Disorganized attachment behaviors in infancy as predictors of brain morphology and peer rejection in late childhood. - Leblanc, Élizabel; Dégeilh, Fanny; Beauchamp, Miriam H.; Bernier, Annie (Cognitive, Affective & Behavioral Neuroscience, 2022)
Studies show robust links between disorganized attachment in infancy and socioemotional maladjustment in childhood. Little is known, however, about the links between disorganized attachment and brain development, and whether attachment-related differences in brain morphology translate into meaningful variations in child socioemotional functioning. This study examined the links between infants' disorganized attachment behaviors toward their mothers, whole-brain regional grey matter volume and thickness, and peer rejection in late childhood. Thirty-three children and their mothers took part in this study. The Strange Situation Procedure was used to assess mother–infant attachment when infants were 18 months old. Magnetic resonance imaging was performed when they were 10 years old to assess cortical thickness and grey matter volumes. Children and teachers reported on peer rejection 1 year later, as an indicator of socioemotional maladjustment. Results indicated that disorganized attachment was not associated with grey matter volumes. However, children who exhibited more disorganized attachment behaviors in infancy had significantly thicker cortices in bilateral middle and superior frontal gyri, and extending to the inferior frontal gyrus, as well as the orbitofrontal and insular cortices in the right hemisphere in late childhood. Moreover, children with thicker cortices in these regions experienced greater peer rejection, as rated by themselves and their teachers. Although preliminary, these results are the first to indicate that disorganized attachment may play a role in cortical thickness development and that changes in cortical thickness are associated with differences in child socioemotional functioning.